(untitled) (Bangladesh Journal of Medical Science, 2013)
Hereditary Ectodermal Dysplasia is an inherited disorder involving skin, teeth, hair and nails. Hypohidrotic ectodermal dysplasia or Anhydrotic ectodermal dysplasia is the most common syndrome among this large group of heriditory disorders. Hypohydrosis/anhydrosis, hypotrichosis and hypodontia constitute the main symptoms of the syndrome. The case of a 28 year old lady with Anhidrotic ectodermal dysplasia and pregnancy with positive family history is described. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 235-237 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14980